If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3n+1=-6-4n
We move all terms to the left:
3n+1-(-6-4n)=0
We add all the numbers together, and all the variables
3n-(-4n-6)+1=0
We get rid of parentheses
3n+4n+6+1=0
We add all the numbers together, and all the variables
7n+7=0
We move all terms containing n to the left, all other terms to the right
7n=-7
n=-7/7
n=-1
| 5x–45=–10 | | -4(v-75)=-48 | | 2(t−5)=48 | | 6x+3=5x–20 | | 40=5(d-72) | | X+6÷3=2x÷4 | | -36=-6(f-78) | | 9(m−3)+3m=7m+43 | | -7=3+2/3x | | -5=x-1/5 | | -5(4x-4)=4(5-5x)+0 | | -4.68=u/6+3 | | 6(1+3m)=-8(5-2m)-4 | | X2+3x+1=4x+3 | | 3a+7a=-5+4a-1 | | 5(x-57)+15=15 | | 2/3(c-1)=2c+1/2 | | 1.1+w/7=-16.4 | | 9.8=6.1+-d | | 8(2y+6)5y=37 | | -2(-4x–8)=-29–7x | | (x+7)+7=180 | | x+2x-12=12-5x | | 3(i-3)-(4i)=-13 | | -2(5x+4)=5(4-2x)-28 | | 4x+5+3x+13=180 | | -4x-15=46 | | 3r–3+2r=13–3r | | 4x-15=56 | | (y+5)^2=2y^2+11y+23 | | -a+7=-11+2a | | 8+4p=-2+6p |